Perkembangan Hukum Jaminan Fidusia di Indonesia Dan Dampaknya terhadap Keamanan Transaksi Bisnis Modern - Risdiana (Fakultas Hukum Universitas Nahdlatul Ulama Nusa Tenggara Barat, 2025)
This study aims to (1) analyze the development of fiduciary guarantee law within the framework of applicable regulations and legal principles, and (2) explain the legal certainty and protection of the parties' rights arising from the application of fiduciary guarantees in business transactions. The method used is normative legal research with a statutory and conceptual approach. The legal material is sourced from primary, secondary, and tertiary legal materials. The analysis is conducted using systematic legal reasoning using legal interpretation, legal theory, and legal principles. The results of the study indicate: first, the regulation of fiduciary guarantees has become increasingly structured through laws, government regulations, ministerial regulations, and their relationship with civil law, thus forming a system of encumbrances, registration, and execution that is more operational and responsive to the needs of modern business practices. Second, in terms of legal protection and certainty, the registration and execution mechanisms provide a firm basis for creditors' rights while simultaneously safeguarding the debtor's right to retain control and use the collateral object. Thus, fiduciary guarantees effectively guarantee legal certainty and balanced protection of the parties' rights and support the security of business transactions.